Assessment of Critical and Strategic Raw Materials for Australia using an AHP-Based Smart Computational Tool - Mammadli, Anvar; Barakos, George; Chang, Ping (SDIMI, 2024)
Due to various factors in different periods of the past two centuries, namely advancing technology, population growth, and even nowadays, the net zero emission goals, the supply and demand of minerals and metals have raised concerns. These concerns pushed many governments to take steps to assess the criticality of such commodities. Determining critical and strategic raw materials and their impact factors is essential to ensuring an efficient and sustainable supply within the mining industry globally. Criticality is generally defined as a combination of a commodity's economic importance and the risk of supply disruption (Buijs et al., 2012; Schrijvers et al., 2020). It is an undeniable fact that raw materials are the backbone of many commercial and industrial sectors globally. No matter the era, their economic importance was one of the primary reasons that had an outstanding impact on their criticality status. Nevertheless, it is impossible to assess and decide according to only one impact factor; criticality is not a singular aspect but rather a complex interplay of economic, environmental, geopolitical, social, and cultural factors (Castro-Sejin et al., 2023). The term 'criticality' has evolved over time. During World Wars I and II, strategic raw materials were deemed critical due to their unavailability during war or national emergencies (U.S. Congress, 1939; Roush, 1939). In the 1950s, as the modern economy grew more complex, challenges related to materials, defence, emergencies, limited supply, and urbanization reshaped the concept of criticality. Since then, 'critical' has been used for emergency situations, while 'strategic raw materials' are reserved for strategic purposes and available cases. This historical context is crucial for understanding the current discourse on criticality (Orchard, 1951). This research holds significant implications for Australia's strategic planning. By identifying and evaluating critical and strategic minerals in a more comprehensive manner, Australia can formulate a more detailed plan to exploit these commodities more efficiently, thereby positioning itself as a key player in global commodities markets.